Macroprolactinoma in an adolescent female with primary amenorrhoea - Ning Zhang; Eleanor White; Tessa Weir; Mark Dexter; Winny Varikatt; Sarah J Glastras (Endocrinology, Diabetes & Metabolism Case Reports, 2024)
Paediatric pituitary adenomas are rare in children and adolescents and differ from adults in both clinical presentation and management. We present the case of a 14-year-old female with primary amenorrhoea secondary to a macroprolactinoma, showing a modest radiological and biochemical response to dopamine agonist (DA) therapy. Despite a 10-month duration of increasing DA therapy, initial symptoms of primary amenorrhoea and hyperprolactinaemia persisted, with new symptoms of weight gain, lethargy and low mood. A transsphenoidal resection of the macroprolactinoma was successfully performed, followed by the initiation of additional hormonal therapy. This case explores the unique challenges of treating a macroprolactinoma refractory to medical management in adolescence.